'What? Olaf is the taxi driver?'. (31st August 2021) - Kim, Younhee; Tse Crepaldi, Yvonne
Abstract : While children's remarkable ability to co-construct spontaneous fantasy narratives in pretend play interaction has been noted, sequential organization embedded in the collaborative construction of narratives have received little research attention. Drawing on an ethnomethodological and conversation analysis perspective, the current study examines the sequential organization of pretend play narratives co-constructed in children's play interaction. Close sequential analysis based on 30 hours of audio and video recordings reveals an array of resources and interactional practices used to construct and maintain the spontaneous narratives. Sequential analysis allows to observe sense-making procedures embedded in the way participating children respond to and develop the storyline. The paper concludes with a reflection on how real-world knowledge informs and regulates the co-constructional process of fantasy narratives.